2008
DOI: 10.1186/1756-9966-27-77
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of IQGAP1 by shRNA inhibits the invasion of ovarian carcinoma HO-8910PM cells in vitro

Abstract: Background: IQGAP1 is a scaffolding protein and overexpressed in many human tumors, including ovarian cancer. However, the contribution of IQGAP1 to invasive properties of ovarian cancer cells remains unknown. Here, we investigated the effect of IQGAP1-specific short hairpin RNA (shRNA) expressing plasmids on metastatic potential of ovarian cancer HO-8910PM cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
(24 reference statements)
2
24
0
2
Order By: Relevance
“…Bogatkevich et al [43] found that silencing the expression of IQGAP1 by siRNA inhibited connective tissue growth factor-induced lung fibroblast migration. RNAimediated knockdown of IQGAP1 expression in human ovarian cancer HO-8910PM cells resulted in a significant decrease in cell invasion and migration [44]. The data presented in this study as well as in the above reports all reveal a promotive role of IQGAP1 in the control of cell migration.…”
Section: Discussionsupporting
confidence: 79%
“…Bogatkevich et al [43] found that silencing the expression of IQGAP1 by siRNA inhibited connective tissue growth factor-induced lung fibroblast migration. RNAimediated knockdown of IQGAP1 expression in human ovarian cancer HO-8910PM cells resulted in a significant decrease in cell invasion and migration [44]. The data presented in this study as well as in the above reports all reveal a promotive role of IQGAP1 in the control of cell migration.…”
Section: Discussionsupporting
confidence: 79%
“…IQGAP1 is overexpressed in colorectal carcinoma (Nabeshima et al, 2002), breast cancer (Jadeski et al, 2008), aggressive ovarian adenocarcinomas (Dong et al, 2008) and gastric cancer (Walch et al, 2008), while IQGAP2 expression is lost in gastric carcinoma (Jin et al, 2008), prostate (Xie et al, 2012) and liver cancer (Schmidt, 2012;Gnatenko et al, 2013). It was also reported that IQGAP1 expression is up-regulated in HCC, characterized by the loss of membrane E-cadherin expression, the cytoplasmic translocation of β-catenin, and the overexpression of nuclear target of β-catenin, cyclin D1 (Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Invasion assays were performed were performed using Transwell system (8-μm pore size, matrigel-coated polycarbonate membrane BD Biosciences, Bedford, MA), as described previously [57]. Briefly, 5 × 10 4 cells resuspended in serum-free medium was added to the upper inserts.…”
Section: Methodsmentioning
confidence: 99%